PENGEMBANGAN TEKNIK DIAGNOSA PARATUBERKULOSIS DENGAN ENZIM LINKED IMMUNOSORBENT ASSAY - Rahmat Setya Adji; Adrijanto Hauferson Angi (Partner, 2009)
Diagnosis Technique Development Paratuberkulosis With Enzyme Linked Immunosorbent Assay. Paratuberculosis (Johne’s Disease) is a chronic granulomatous enteritis diseases of ruminants caused by Mycobacterium paratuberculosis. The disease spreads by faeces with clinical signs of progressivediarrhoae and weight losses. Diagnostic kit for paratuberculosis testing be needed for control and monitoring. The aim of research for develop of ELISA to diagnosis of paratuberculosis desease. The ELISA was developed have 0,29 of a cut – off value with both positive and negative control be tested by using commercial ELISA kit (IDEXX), showed good result. The result of ELISA 80 serum sample of dairy cattle from Kaliadem, Sleman-Daerah Istimewa Yogyakarta, showed negativeparatuberculosis (mean of OD 0,162 ± 0,015). Keywords: Paratuberculosis, ELISA